Multipoint problem for typeless factorized differential operators - Ptashnik, B. I.; Sylyuha, L. P. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We analyze the well-posedness of a problem with multipoint conditions in the time variable and periodic conditions in the spatial coordinates for differential operators decomposable into operators of the first order with complex coefficients. We establish conditions for the existence and uniqueness of the classical solution of the problem under consideration and prove metric theorems for the lower estimates of small denominators appearing in the process of construction of the solution.